Are Wages Equal Across Sectors of Production? A Panel Data Analysis for Tradable and Non-Tradable Goods - Achim Schmillen (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
The assumption that national labor markets are homogenous across tradable and non-tradable goods is common in multisector (open-economy) macro models and crucial for the prominent Balassa-Samuelson hypothesis. This study tests it with a novel method to distinguish the tradable and non-tradable sectors grounded in economic theory, modern empirical methods and a large and detailed macro data set. It nds that both the internal relationship between productivity and wages in the tradable and non-tradable sectors postulated by the Balassa-Samuelson hypothesis and its external transmission mechanism are rejected.
Keywords: F31; F41; 330; Balassa-Samuelson; Wage equalization; Tradability; Lohnstruktur; Branche; Handelbares Gut; Nicht-handelbares Gut; Schätzung; Welt; Balassa-Samuelson Effekt; Kritik